2019
DOI: 10.5539/ijps.v11n3p39
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Prevalence of Substance Abuse among Students of Higher Education Institutions in Benue State, North- Central Nigeria: Implications for Counseling

Abstract: The Investigation was directed towards the prevalence of substance abuse among students of higher education institutions, Benue State North – Central Nigeria. In order to undertake the research, one research question and one hypothesis were formulated to guide the study. The researcher made use of “Prevalence of Substance Abuse among Students Questionnaire” (POSAASQ) to obtain information for the research. The instrument was made up of twenty items. Students responded to substance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Onofa et al, (2016) andOnoyase (2019) reported alcohol as the substance used most among tertiary students in Abeokuta and Benue state respectively. This justifies that the pattern of drug use varies from one locality to another.…”
mentioning
confidence: 99%
“…Onofa et al, (2016) andOnoyase (2019) reported alcohol as the substance used most among tertiary students in Abeokuta and Benue state respectively. This justifies that the pattern of drug use varies from one locality to another.…”
mentioning
confidence: 99%